Features of ensuring the accuracy of coordinated dimensions when using typical flow sheets - Тріщ, Роман Михайлович; Бурдейна, Вікторія Михайлівна (Technology audit and production reserves, 2014)
When developing any design it is mandatory to carry out dimensional analysis of all design solutions. The main aspect in this case is primarily calculating output parameters coordinated dimensions of the hole. Two typical flow sheets: cutting tool guiding and noncutting tool guiding are investigated. Analytical dependences for calculating the accuracy of coordinated dimensions for typical flow sheets are presented in the paper. Dependences for determining the interaxle dimension, dimension from the base, positional variation are proposed. The specific weight of the components of the geometric error in the non-cutting tool-guiding and cutting tool-guiding flow sheets is determined. Calculated values of total processing error using modular machine tooling are defined. Studies have shown that the accuracy of coordinating dimensions and positional variations depends on the total geometric accuracy of machine flow sheet elements and total elastic deformations. This will allow to set the optimum accuracy of processing major parts, defining the output geometric parameters of modular machines and select the desired assembly method.